Chlamydia screening by community pharmacists: a qualitative study. Issue 1 (10th January 2011) - Dabrera, Gavin; Pinson, David; Whiteman, Steve
Abstract : Background and methodology: The National Chlamydia Screening Programme offers opportunistic screening for genital Chlamydia trachomatis infection to young people aged 15–24 years in England. Screening packs are available in many different settings, including community sexual health clinics, colleges and community pharmacies. This article focuses on screening through community pharmacies. Currently, pharmacies provide only a small proportion of screening nationally despite the assumption that community pharmacies are an ideal location to undertake chlamydia screening. This article reports on semistructured interviews undertaken with a sample of 10 pharmacists offering chlamydia screening in Greenwich, London, UK in order to understand the issues facing pharmacists in offering chlamydia screening. Results: Participants had good awareness of the importance of chlamydia infection and the need for screening. The majority were supportive of it, although some were concerned about approaching some younger individuals. Many pharmacists only raised opportunistically the provision of free chlamydia screening when customers were attending for emergency hormonal contraception. The pharmacists felt it was more difficult to discuss the subject of chlamydia screening with customers attending for non-sexual health-related services. The local chlamydia screening programme had undertaken other initiatives including mail outs. Some pharmacists had broached the subject of chlamydia screening but had discovered customers already had a screening pack at home. Discussion and conclusions: These findings have highlighted challenges in opportunistically offering chlamydia screening to young people in community pharmacies. These challenges can be overcome through a combination of training and service innovation, in order to capitalise on the potential of community pharmacies to contribute to this important sexual health service.